Contemporary Concepts for the Bilateral Cleft Lip and Nasal Repair - Khosla, Rohit K.; McGregor, Jyoti; Kelley, Patrick K.; Gruss, Joseph S. (Seminars in Plastic Surgery, 2012)
The bilateral cleft lip and nasal deformity presents a complex challenge for repair. Surgical techniques continue to evolve and are focused on primary anatomic realignment of the tissues. This can be accomplished in a single-stage or two-stage repair early in infancy to provide a foundation for future growth of the lip and nasal tissue. Most cleft surgeons currently perform a single-stage repair for simplifying patient care. Certain institutions utilize presurgical orthopedics for alignment of the maxillary segments and nasal shaping. Methods for the bilateral cleft lip repair are combined with various open and closed rhinoplasty techniques to achieve improved correction of the primary nasal deformity. There is recent focus on shaping the nose for columellar and tip support, as well as alar contour and alar base position. The authors will present a new technique for closure of the nasal floor to prevent the alveolar cleft fistula. Although the alveolar fistula is closed, alveolar bone grafting is still required at the usual time in dental development to fuse the maxilla. It is paramount to try and minimize the stigmata of secondary deformities that historically have been characteristic of the repaired bilateral cleft lip. A properly planned and executed repair reduces the number of revisions and can spare a child from living with secondary deformities.
Keywords: bilateral cleft lip; bilateral cleft lip and palate; cleft nasal deformity; primary bilateral cleft lip repair; primary cleft rhinoplasty